Understanding the Effects of Online Learning Readiness, Motivation, Self-Regulation, and Attitudes Toward E-Learning on Perceived Learning During Distance Education - Mustika, Ninette Putri; Royanto, Lucia R. M. (UI Scholars Hub, 2024)
In the context of the COVID-19 pandemic in Indonesia, this research examines the impact of online learning readiness, academic motivation, self-regulated learning, and attitudes toward e-learning on undergraduate students' perceived learning experiences in distance education. Employing a quantitative design, this study analyzes responses from a sample of 540 undergraduate students using conditional process analysis. The methodology includes the use of structured questionnaires as instruments to assess the constructs of online learning readiness, academic motivation, self-regulated learning, and attitudes towards e-learning. The findings reveal that online learning readiness directly and indirectly influences perceived learning through the mediating role of academic motivation. Additionally, self-regulated learning and positive attitudes toward e-learning amplify the impact of academic motivation on perceived learning, though they do not condition the indirect effect of online learning readiness on perceived learning. This suggests that well-prepared and academically motivated students are more likely to perceive their learning positively in online settings.